Effects of one‐legged high‐intensity interval training on insulin‐mediated skeletal muscle glucose homeostasis in patients with type 2 diabetes. (14th February 2019) - Dela, Flemming; Ingersen, Arthur; Andersen, Nynne B.; Nielsen, Maria B.; Petersen, Helga H. H.; Hansen, Christina N.; Larsen, Steen; Wojtaszewski, Jørgen; Helge, Jørn Wulff
Abstract: Aim: To examine the effect of high‐intensity interval training (HIIT) on glucose clearance rates in skeletal muscle and explore the mechanism within the muscle. Methods: Ten males with type 2 diabetes mellitus (T2DM) and ten matched healthy subjects performed 2 weeks of one‐legged HIIT (total of eight sessions, each comprised of 10 × 1 minute ergometer bicycle exercise at >80% of maximal heart rate, interspersed with one min of rest). Insulin sensitivity was assessed by an isoglycaemic, hyperinsulinaemic clamp combined with arteriovenous leg balance technique of the trained (T) and the untrained (UT) leg and muscle biopsies of both legs. Results: Insulin‐stimulated glucose clearance in T legs was 30% higher compared with UT legs in both groups due to increased blood flow in T vs UT legs and maintained glucose extraction. With each training session, muscle glycogen content decreased only in the training leg, and after the training, glycogen synthase and citrate synthase activities were higher in T vs UT legs. No major changes occurred in the expression of proteins in the insulin signalling cascade. Mitochondrial respiratory capacity was similar in T2DM and healthy subjects, and unchanged by HIIT. Conclusion: HIIT improves skeletal muscle insulin sensitivity. With HIIT, the skeletal muscle of patients with T2DM becomes just as insulin sensitive as untrained muscle in healthy subjects. The mechanism includes oscillations in muscle glycogen stores and a maintained ability to extract glucose from the blood in the face of increased blood flow in the trained leg.